Anti-dsDNA, anti-Sm antibodies, and the lupus anticoagulant: significant factors associated with lupus nephritis. Issue 6 (1st June 2003) - Alba, P; Bento, L; Cuadrado, M J; Karim, Y; Tungekar, M F; Abbs, I; Khamashta, M A; D'Cruz, D; Hughes, G R V
Abstract : Background: Lupus nephritis (LN) is a common manifestation in patients with systemic lupus erythematosus (SLE). Autoantibodies and ethnicity have been associated with LN, but the results are controversial. Objective: To study the immunological and demographic factors associated with the development of LN. Patients and methods: A retrospective case-control study of 127 patients with biopsy-proven LN, and 206 randomly selected patients with SLE without nephritis as controls was designed. All patients had attended our lupus unit during the past 12 years. Standard methods were used for laboratory testing. Results: Patients with LN were significantly younger than the controls at the time of SLE diagnosis (mean (SD) 25.6 (8.8) years v 33.7 (12.5) years; p<0.0001). The proportion of patients of black ethnic origin was significantly higher in the group with nephritis (p=0.02). There were no differences in sex distribution or duration of follow up. A higher proportion of anti-dsDNA, anti-RNP, anti-Sm, and lupus anticoagulant (LA) was seen in the group with nephritis (p=0.002; p=0.005; p=0.0001; p=0.01, respectively). In univariate, but not in multivariate, analysis male sex and absence of anti-dsDNA were associated with earlier onset of renal disease (p=0.03; p=0.008). In multivariate analysis the only factors associated with nephritis were younger age at diagnosis of SLE, black race, presence of anti-dsDNA, anti-Sm, and LA. No demographic or immunological associations were seen with WHO histological classes. Conclusions: Young, black patients with anti-dsDNA, anti-Sm antibodies, and positive LA, appear to have a higher risk of renal involvement. These patients should be carefully monitored for the development of LN.